Islam dan Pembangunan Karakter: (Analisis Konsep dan Praktik Pendidikan Agama Islam dalam Membentuk Insan yang Beriman dan Berakhlak) - Najamudin Najamudin; Surahman Hidayat (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
Islamic religious education has a fundamental role in forming people who are faithful and have noble character. The concept of Islamic education is based on the values ​​of monotheism, the exemplary behavior of the Prophet Muhammad SAW, and the teachings of the Qur'an and hadith which emphasize the importance of morality in individual and social life. This study analyzes the concept and practice of Islamic religious education in building character through a qualitative approach with literature study methods, observation, and interviews. The results of the study show that Islamic education is implemented through various methods, including cognitive learning, habituation of worship, role models, and the role of family and social environment. Islamic education does not only focus on mastering religious knowledge but also on internalizing moral and ethical values ​​that shape the personality of Muslims who have noble character. Therefore, optimizing Islamic religious education is very important in facing moral challenges in the modern era.